An Examination of Moderating Effects of Demographics on Bullying to Turnover Intention: A Case of Korean Kitchen Employees in Upscale Hotels (Journal of Organizational Psychology, 2020)
The primary objective of this research is to identify the relationship between bullying and turnover intentions of kitchen workers. The study further investigates moderating effects of selected demographic variables on turnover intention when employees experience bullying. Cross-sectional survey data was collected from 288 kitchen workers from 12 upscale hotels in Korea. The results of the study identified several important demographic characteristics that determine employees’ intentions to leave. Practical recommendations are outlined for managers involved in human resources management. The study offers valuable insights for prospective employers to develop on-going programs to create a positive working environment within the hospitality industry.
Keywords: Organizational Psychology; bullying; turnover intention; moderating effects of demographics; social isolation; psychological harassment; professional status; hotel kitchen